2022
DOI: 10.26444/aaem/157357
|View full text |Cite
|
Sign up to set email alerts
|

Expectations of patients with hepatitis C from family physicians – a Polish example

Abstract: Introduction. In Poland, approximately 1.9% of the general population is infected with Chronic hepatitis C (HCV), which develops in about 70-80% of infected patients who require constant care from family physicians. Objective. The aim of the study was to define the kinds of expectations of patients with chronic HCV from family physicians. Materials and method. The study included 220 patients with HCV, and was conducted using a dignostic survey, the Patient Request Form (PRF) and an author-constructed questionn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 18 publications
(20 reference statements)
0
3
0
Order By: Relevance
“…A study by Sierpińska showed that patients with somatic diseases (hepatitis C) also experience difficulties with contacts with a family physician. Their expectations concern an explanation of the essence of the disease and procedures concerning examinations, treatment, and rehabilitation [31]. A study by Ocoro concerning the overall prevalence of disability and according to the type of disability, and access to health care according to the type of disability demonstrated that locomotor disability was most prevalent among people at middle age (18.1%), and those aged 65 and older.…”
Section: Discussionmentioning
confidence: 99%
“…A study by Sierpińska showed that patients with somatic diseases (hepatitis C) also experience difficulties with contacts with a family physician. Their expectations concern an explanation of the essence of the disease and procedures concerning examinations, treatment, and rehabilitation [31]. A study by Ocoro concerning the overall prevalence of disability and according to the type of disability, and access to health care according to the type of disability demonstrated that locomotor disability was most prevalent among people at middle age (18.1%), and those aged 65 and older.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the existing evidence base is fragmentary and difficult to interpret scientifically. This also applies to persons with chronic infectious diseases, mainly hepatitis C [42,43]. There is also little data on the effectiveness of services and health systems for patients suffering from multi-morbidity.…”
Section: Description Of the State Of Knowledgementioning
confidence: 99%
“…The intestinal microbiota plays an important role in normal gut function and maintaining host health. [13][14][15][16][17][18][19][20][21][22][23][24]…”
Section: Introductionmentioning
confidence: 99%